Significance of Harmonic Contents with Respect to the Timbre of the Violoncello - Liu, Li Yoon (2002)
Harmonic contents (harmonic or inharmonic partials) is an important waveform characteristic that influences the timbre of musical tones. The first part of this research is aimed at finding out (through waveform analysis) the harmonic and inharmonic partials of four sampled violoncello (or cello) C#3 tones, each played using a different technique. The four different techniques studied are 'arco', 'spiccato', 'pizzzicato' and 'tremolando'. From the results of the waveform analysis, the difference in timbre between the four different playing techniques of the cello could be understood by comparing the harmonic contents of the four cello tones. The results of the waveform analysis generally showed that the four different playing techniques have different number of harmonic and inharmonic partials in their spectra. Both the 'spiccato' and 'tremolando' techniques produced more inharmonic compared to harmonic partials while the 'arco' technique produced more harmonic compared to inharmonic partials. The 'pizzicato' technique produced only harmonic partials. The results of the waveform analysis is then used in the second part of this research that is aimed at finding out the significance of various groups of harmonic or inharmonic partials in contributing to the timbre of the cello through a listening test. For this test, the results of the waveform analysis are used to modify the harmonic contents of the four cello tones. The timbres of the modified cello tones are then compared with the original cello tones by using short music sequences. Comparisons are then made between the four different techniques by using tables and graphs. Results indicate that different groups of harmonic or inharmonic partials affect the timbre of the cello in different ways. In other words, some groups of harmonic or inharmonic partials are more significant to the timbre of the cello compared to other groups. Besides, the timbres of the four different playing techniques are influenced by the harmonic contents modifications differently. The results generally showed the 'spiccato' technique as the technique that is influenced most significantly and the 'pizzicato' technique as the. technique that is influenced least significantly in timbre by the harmonic contents modifications executed. The timbres of both the 'arco' and 'tremolando' techniques are influenced moderately by the harmonic contents modifications. However, the timbre of the cello 'arco' technique is influenced more significantly by the harmonic contents modifications compared to the 'tremolando' technique.